Synthesis and antimycobacterial activity of N-(2-aminopurin-6-yl) and N-(purin-6-yl) amino acids and dipeptides. Issue 11 (1st June 2016) - Krasnov, Victor P.; Vigorov, Alexey Yu.; Musiyak, Vera V.; Nizova, Irina A.; Gruzdev, Dmitry A.; Matveeva, Tatyana V.; Levit, Galina L.; Kravchenko, Marionella A.; Skornyakov, Sergey N.; Bekker, Olga B.; Danilenko, Valery N.; Charushin, Valery N.
Graphical abstract: Abstract: Synthetic routes to novel N -(purin-6-yl)- and N -(2-aminopurin-6-yl) conjugates with amino acids and glycine-containing dipeptides were developed. In vitro testing of 42 new and known compounds made it possible to reveal a series of N -(purin-6-yl)- and N -(2-aminopurin-6-yl) conjugates exhibiting significant antimycobacterial activity against Mycobacterium tuberculosis H37Rv, Mycobacterium avium, Mycobacterium terrae, and multidrug-resistant M. tuberculosis strain isolated from tuberculosis patients in the Ural region (Russia). N -(2-Aminopurin-6-yl)- and N -(purin-6-yl)-glycyl-( S )-glutamic acids were the most active compounds.